Harnessing technology to empower mature age learners - Quinton, Stephen; Dreher, Heinz; Fisher, Darrell; Houghton, P. (Curtin University of Technology, 2006)
The use of new online technologies and environments that combine innovation and a thorough understanding of educational theory to derive new models of learning are regarded as priority development areas in many countries including the European Union and Australia. In this paper we report on a project which is building 'Knowledge Spaces' using learning object technology to develop educationally sound online learning environments. Learning object technology promotes the use and re-use of educational content, and coupled with personalised environments and adaptive user interfaces, we are able to deliver relevant educational experiences to a diverse range of individual learners and communities of learners. We have developed a design evaluation model based on an extension of Reeve?s pedagogical dimensions, and tailored it cater for the diverse and flexible needs of mature age learners. By understanding the learner preferences, and the needs and requirements of mature aged people, we argue it is possible to provide opportunities for learning using the online environment that will improve the quality, variety and relevance of learning. To assess the attainment of the educational objectives is normally a time consuming task, but in our technological environment we propose to match the learning modules with automatically generated test modules through the use of Automated Essay Grading technology, which grades unseen text essays and provides feedback in numeric and interactive visual form. The project outcomes will result in the application of new methodologies for the effective implementation of complex, intelligent learning environments with a view to constructing an online learning environment tailored to the specific needs of mature age learners..